2015
DOI: 10.1515/kom-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Selected types of corrosion degradation of pipelines

Abstract: The paper deals with corrosion degradation of gas pipeline. Pipelines play very important role as means transporting gas media over long distances from producers to end-users. Gas pipelines present a risk of potential corrosion degradation that can result in their failure. Corrosion on internal surfaces of steel pipes takes place in CO2, H2S, H2O and chloride environment. Degradation of steel results in loss of mechanical properties, reduction in thickness and ultimate perforation and failure. Corrosion is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Corrosion can cause damage to both the inside and exterior layers of a pipeline and image-based inspection by AUS allows for the detection of exterior corrosion. Hagarova et al [8] examined the types of corrosion and prevention mechanisms that often involve coatings and cathodic protection. The outer surfaces of pipelines are additionally protected by protective barriers, metal and non-metal coatings, glass fiber, rubber, and epoxide designed to last for the duration of the pipeline's life [7][8][9].…”
Section: Pipeline Materials Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrosion can cause damage to both the inside and exterior layers of a pipeline and image-based inspection by AUS allows for the detection of exterior corrosion. Hagarova et al [8] examined the types of corrosion and prevention mechanisms that often involve coatings and cathodic protection. The outer surfaces of pipelines are additionally protected by protective barriers, metal and non-metal coatings, glass fiber, rubber, and epoxide designed to last for the duration of the pipeline's life [7][8][9].…”
Section: Pipeline Materials Degradationmentioning
confidence: 99%
“…Hagarova et al [8] examined the types of corrosion and prevention mechanisms that often involve coatings and cathodic protection. The outer surfaces of pipelines are additionally protected by protective barriers, metal and non-metal coatings, glass fiber, rubber, and epoxide designed to last for the duration of the pipeline's life [7][8][9]. However, the degradation of the outer surface of the pipeline gains an electrochemical nature.…”
Section: Pipeline Materials Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors Antony et al (2007), Cetin and Aksu (2009) reported that sulphate reducing bacteria (SRB) acting under anaerobic conditions is responsible for MIC corrosion. SRB of the following genera are mostly involved: Desulphotomaculum species, Achromobacter species, Flavobacterium species and others (Hagarová et al, 2015). They can grow under a pH range from 4.0 to 9.5 and tolerate pressure up to 500 atm (AlAbbas et al, 2013), and most SRB exist in a temperature range from 25°C to 60°C (Madigan et al, 2008).…”
Section: Microbiologically Induced Corrosionmentioning
confidence: 99%
“…Corrosion becomes a principal problem for some industries in the world, mainly in oil and gas industries. Transportation of fluids containing crude oil, natural gas, and corrosive substances creates rust in the inner part of the pipeline by electrochemical reactions [4]. Repairing and replacement of the rusted pipeline required a very expensive cost and spent a lot of time.…”
Section: ■ Introductionmentioning
confidence: 99%